Factors of formation and development of Russian management thought as main components of the Russian model of management in XX century - A. V. Dvoynev (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the actual problem of identifying problems and prospects for the development of the methodological framework in the study of the essence and features of the Russian management model. The article reveals the essence and features of the factors that influenced the development of Russian management thought and the Russian management model in the XX century, the prospects for further study of the system of labor indicators are revealed